My Hero Academia. Vol. 26, The high, deep blue sky - 1986-; Cook, Caleb D. (Shonen Jump manga., 2021)
While preparing for a big villian attack, Eraser Head and Present Mic pay a visit to Tartarus prison, while Midoriya, Bakugo, and Todoroki begin training under Endeavor in order to become fighters who can stand on their own.